Axial compressive performance of ultra-high strength concrete-filled dual steel tubular short columns with outer stiffened tubes and inner circular tubes. (April 2023) - Zhang, Jun-Hua; Shao, Yong-Bo; Hassanein, M.F.; Patel, V.I.
Abstract: Previous literature shows that studies of ultra-high strength concrete-filled dual steel tubular (UHS-CFDST) short columns under concentric compression are rare, and there is no relevant research on ultra-high strength concrete-filled dual stiffened steel tubular (UHS-CFDSST) short columns. In addition, existing design specifications do not include ultra-high strength concrete (UHSC). Therefore, the axial compressive response and resistance of UHS-CFDSST short columns are investigated herein. First, the behaviour of CFDSST columns with normal-strength concrete (NSC) was replicated by finite element (FE) modelling using ABAQUS software. Additionally, the experimental results of square and circular ultra-high strength concrete-filled steel tubular (UHS-CFST) short columns were collected from the available literature, and finite element (FE) modelling is performed accordingly. The results showed that the applied concrete constitutive model is suitable for UHSC and the modelling strategy for UHS-CFST columns and CFDSST columns with NSC is suitable for UHS-CFDSST short columns. Accordingly, parametric studies were carried out on UHS-CFDSST to investigate the effects of geometrical and material properties of different steel and concrete components on the performance of these columns. It was found that the strength of the sandwiched concrete has the greatest effect on the resistance of the columns compared to the other parameters considered. Finally, the axial resistance of the UHS-CFDSST short columns was compared to the resistances calculated by using the European, British and Chinese codes, and it was found that the Chinese code gives the best results. Highlights: FE model for UHS-CFDSST short columns under axial loading is presented. FE models of the UHS-CFDSSTs are validated against existing experimental results. The sandwiched concrete strength has the greatest effect on the resistance of the columns. The Chinese design model is shown to predict well the strengths of UHS-CFDSST columns.